Identification of climate changes based on antropogenic transformation of landscapes - Polishchuk, Liydmila Borisivna; Reshetchenko, Svitlana Ivanivna; Cherkashyna, Nadyia Ivanivna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Formulation of the problem. Functioning of natural geosystems is aimed at preserving their structure, but economic activity leads to imbalances, decreases in order, loss of internal organization and the inability to maintain the necessary stabilization. Analysis of previous research. Studies of the last decades have shown that the climatic conditions of Ukraine can be unfavorable for the life and economic activity of the society. Problems of further research. To find the solution to the problem of preserving the ability of the biosphere to self-regulation, self-restoration by optimizing anthropogenic load on natural systems is very important. Identification of climate change factors is aimed at finding the most active sources of environmental impact in order to determine the real threat of global climate change. The purpose of the research is to determine the causes, areas of initial formation, further development of negative meteorological processes and phenomena on the territory of Kharkiv region during the last decades and to study parameters and causes of air masses transformation, changes in their properties and various resistance to anthropogenic impact. Research methods are observation with the help of various devices and technical means. An integrated approach using field-based observations and technology of climatic series analysis with the help of statistical methods for climate information processing, characterized by high accuracy, allow us to determine their spatial-temporal features and future projections to the natural environment. Presentation of the main research material. Optimal strategic socio-economic development of the regions requires identification of specific links between natural and socio-economic entities, as well as studying large-scale and profound by the consequences violations of the ecosystem at the planetary level - the biosphere and its components. There is a general tendency towards directed climate change, the so-called "global warming", which threatens natural landscapes, upsetting and destroying them. Practical value. There are causal relationships between climatogenic changes, influence of human activity and the reaction of landscapes to them. This is manifested in creation of a variety of transformed landscapes (agrarian, residential, industrial). The consequence of anthropogenic transformations is the change in the parameters and characteristics of the components of nature. Research results. Indicators are the basis for information blocks concerning decision-making in the areas of socio-economic development. Climate parameters of a certain territory may differ from zonal ones and in combination with anthropogenic transformation affect the general condition of the landscapes, lead to the intensification of adverse hydrometeorological and exogenous geodynamic processes and phenomena (erosion, deluvial processes, landslides, suffusion, deflation, flooding.